The Tradition of Hibah Andum Berkat as a Substitute for Inheritance: A Perspective of Justice and the Interconnectedness of Maslahah (A Case Study of the Mojoroto Community, Kediri, East Java) - Rohman, Baitur; Rosyadi, Imam; Thohari, Ilham; Aziz, Muhammad Abdul; Shokri, Nurul Najihah Binti Mohamad (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
Hibah andum berkat, a substitute for inheritance, is a hereditary tradition practised by the Mojoroto community in Kediri, East Java. This tradition is regarded as a preventive measure to avoid family conflicts by ensuring justice among the heirs in distributing parental assets. It is characterized by an equal division between male and female heirs, with an additional share granted to the child who cared for the parents during their lifetime. This study aims to examine the concept of justice embedded in the implementation of hibah andum berkat as an alternative to inheritance, analyzed through the perspectives of justice and the interconnectedness of maslahah (public interest). This research is expected to contribute an alternative model for distributing parental assets that upholds a greater sense of justice. The study employs an empirical legal approach using a descriptive-qualitative method. The findings reveal that: (1) The tradition of hibah andum berkat as a substitute for inheritance is more socially acceptable, as it reflects proportional justice and promotes equality, thereby maintaining peace among heirs. (2) From the perspective of maslahah interconnectivity, this tradition falls within the scope of maqāṣid al-sharī‘ah, particularly ḥifẓ al-māl (the protection of wealth), which is interconnected with the other components of al-uṣūl al-khamsah.